Assessing How Product Quality and Price Affect Buying Behavior at Retail Sector - Hendi Hendian Hidayat; Dudung Juhana; Boy Suzanto; Firmansyah Damanik (P3M, STIE Pasundan, Bandung, Indonesia., 2025)
This research highlights the main issue related to the intensifying competition in the market, which requires producers to be more sensitive to changes across various aspects. The primary aim of this study is to analyze consumer behavior in purchasing decisions and how this influences the company’s marketing strategy. The research employs both qualitative and quantitative analysis based on sales data and consumer surveys. The findings indicate that consumer purchasing decisions are affected by product quality and pricing, with a noted decline in purchases due to these issues. The novelty of this research emphasizes the importance of understanding consumer behavior for formulating more effective marketing strategies. The implications of this study suggest that companies should adapt to market demands and enhance product quality and pricing to meet consumer expectations and maintain their market position.